Effect of flupyradifurone on zebrafish embryonic development. (15th September 2021) - Zhong, Keyuan; Meng, Yunlong; Wu, Juan; Wei, You; Huang, Yong; Ma, Jinze; Lu, Huiqiang
Abstract: Evaluation of the toxicity of pesticide residues on non-target organisms in the ecosystem is an important part of pesticide environmental risk assessment. Flupyradifurone is a new type of butenolide insecticide produced by Bayer, who claims it to be "low toxic" to non-target organisms in the environment. However, there is little evidence in the literature to show how flupyradifurone affects aquatic organism development. In the current study, zebrafish embryos were treated with 0.1, 0.15, and 0.2 mg/mL of flupyradifurone within 6.0–72 h past fertilization (hpf). We found that the half-lethal concentration (LC50 ) of flupyradifurone for zebrafish embryos at 96 hpf was 0.21 mg/mL. Flupyradifurone decreases the heart rate, survival rate, and body length of zebrafish embryos. The flupyradifurone treatment also led to the failure of heart looping, and pericardial edema. Moreover, flupyradifurone increased the level of reactive oxygen species (ROS) and decreased the enzymatic catalysis of catalase (CAT) and superoxide dismutase (SOD). Alterations were induced in the transcription of apoptosis-related genes ( bcl-2, bax, bax/bcl-2, p53 and caspase-9 ) and the heart development-related genes ( gata4, myh6, nkx2.5, nppa, tbx2b, tbx5 and vmhc ). In the current study, new evidences have been provided regarding the toxic effects of flupyradifurone and the risk of its residues in agricultural products and the environment. Graphical abstract: Image 1 Highlights: Flupyradifurone causes a decrease in the heart rate, body length of zebrafish. The exposure flupyradifurone leads to failure of heart looping and pericardial edema. Flupyradifurone increases ROS levels and decreases the activity of SOD and CAT. Flupyradifurone alters the transcription levels of apoptosis and heart related genes.